HUBUNGAN PERILAKU IBU TERHADAP PEMELIHARAAN KESEHATAN GIGI ANAK DENGAN KEJADIAN EARLY CHILDHOOD CARIES (ECC) PADA ANAK PENDIDIKAN USIA DINI (PAUD) DI WILAYAH KERJA PUSKESMAS ANDALAS KECAMATAN PADANG TIMUR KOTA PADANG - Wulandari Liza Putri; Febrian Febrian (Faculty of Dentistry Universitas Andalas, 2014)
Early Childhood Caries (ECC) is dental disease in preschool children that becomes a huge problem whole the world. In USA, prevalence of ECC is 41% and 90% in Indonesia, but actually WHO Oral Health Goal decided 90% of children must have to be caries free. One of risk factor of ECC in preschooler is mothers behavior. The aim of this research is to provide relationship between mothers behavior toward oral health maintenance and ECC among preschool children of informal education in Andalas Social Health Centre working area East Padang Subdistrict Padang City.This research used cross sectional study design. Samples were preschool children of informal education and respondents were their mothers amount 81 people. Preschoolers underwent a comprehensive dental examination while mothers were investigated used questionnaire that explored knowledge, attitudes, and behavior toward preschool oral health maintenance. Statistic analysis of this research were univariat analysis and bivariat analysis used chi-square test and p<0,05.The result indicates that 79% children suffered from ECC, mothers knowledge of 91,4% in high category, mothers attitudes of 48,1% in negative category, and mothers behavior was in bad category of 43,2% toward oral health maintenance. There is no relationship between mothers behavior toward oral health maintenance and ECC.Suggested to health workers to do preschool children dental screening periodically and give dental health education to mothers who have preschool children so that ECC can be decreased.